2020
DOI: 10.1093/heapro/daaa102
|View full text |Cite
|
Sign up to set email alerts
|

Better health indicators of FitSpirit participants meeting 24-h movement guidelines for Canadian children and youth

Abstract: Summary This study aims to determine the proportion of girls who meet the recommendations for moderate-to-vigorous physical activity (MVPA), screen time and sleep duration among FitSpirit participants and evaluate the associations of these recommendations with perceived health-related quality of life (QOL), perceived health, physical activity (PA), self-efficacy and body mass index. Cross-sectional analyses of FitSpirit data were performed. All variables were collected through an online question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…A total of 387,437 participants (49% of boys and 51% of girls) aged 3–18 years were included in this systematic review and meta-analysis, of which 11,768 were preschoolers (3–5 years; 3%), 76,928 (6–12 years; 20%) were children, and 298,741 (13–18 years; 77%) were adolescents. Twenty-six studies were conducted with preschoolers only, 8 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 13 studies with children only, 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 17 studies with adolescents only, 11 , 12 , 60 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 and 7 studies with both children and adolescents. 9 , 10 , 76 , 77 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 387,437 participants (49% of boys and 51% of girls) aged 3–18 years were included in this systematic review and meta-analysis, of which 11,768 were preschoolers (3–5 years; 3%), 76,928 (6–12 years; 20%) were children, and 298,741 (13–18 years; 77%) were adolescents. Twenty-six studies were conducted with preschoolers only, 8 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 13 studies with children only, 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 17 studies with adolescents only, 11 , 12 , 60 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 and 7 studies with both children and adolescents. 9 , 10 , 76 , 77 ...…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the measurement of the 3 components of the 24-Hour Movement Guidelines, physical activity was obtained by device-based measures in 37 studies, 8 , 9 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 46 , 47 , 49 , 51 , 52 , 53 , 54 , 55 , 59 , 64 , 65 , 73 , 76 , 78 , 81 self-reported measures in 22 studies, 10 , 11 , 12 , 50 , 57 , 58 , 60 , 61 , 62 , 63 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 74 , 75 , 77 , 79 , 80 and parent-reported measures in 4 studies. 32 , 45 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Studies among children and youth have suggested that adhering to recommendations for a higher number of individual movement behaviours (e.g. for 3 vs for 2, or for 2 vs for 1) is associated with greater health benefits [ 19 , 20 ]. However, for adult populations, such evidence is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…However, for girls in the unadjusted regression models, our findings highlighted that only sleep time combined with physical activity and screen behaviors were important for quality of life. In this sense, there are differences in the results obtained by previous studies [ 20 , 43 , 44 ]. Furthermore, in contrast to our findings, the studies by Guimarães et al [ 43 ] and Hesketh et al [ 44 ] showed a higher adherence to movement behaviors.…”
Section: Discussionmentioning
confidence: 60%
“…In this sense, there are differences in the results obtained by previous studies [ 20 , 43 , 44 ]. Furthermore, in contrast to our findings, the studies by Guimarães et al [ 43 ] and Hesketh et al [ 44 ] showed a higher adherence to movement behaviors. More specifically in line with our results, Guimarães states that girls show more ease in complying with sleep recommendations compared to their peers.…”
Section: Discussionmentioning
confidence: 60%